Hydrocarbons and heavy metals fixed to the lift station sediments of the Paris agglomeration - Rocher, V.; Gasperi, J.; Azimi, S.; Celaudon, T.; Moilleron, R.; Chebbo, G. (Houille Blanche, 2004)
During rain events, great quantities of hydrocarbons (aliphatic and aromatic) and heavy metals enter the combined sewer by way of roof and road runoff. The decrease of these inputs, necessary to the combined sewer overflow reduction, requires knowledge of pollutant nature and origin. This work, focused on lift station sediments, aims to characterised the contents and fingerprints of pollutants associated to road runoff. Hydrocarbon contamination levels, calculated at 80 and 24 mug.g(-1) dw for aliphatic and aromatic compounds, are of the same order of magnitude than those reported in the literature. In the same way, heavy metal contamination levels are in a good agreement with previous studies. Nevertheless, a decrease of Pb contents, induced by the recent restriction of the Pb traffic emission, and an increase of Cu contents, probably linked to the occurrence of intensive brake lining abrasion, were noticed Moreover, hydrocarbon fingerprints underline the variability of the hydrocarbon origin. Indeed, aliphatic distributions reflect the combination of biologic (vegetal) and petrogenic (lubricating oils, gasoline, etc.) inputs, while aromatic distributions indicate a major pyrolytic origin with traces of petrogenic contaminations.